2004
DOI: 10.1038/sj.ejhg.5201319
|View full text |Cite
|
Sign up to set email alerts
|

Y chromosome evidence for a founder effect in Ashkenazi Jews

Abstract: Recent genetic studies, based on Y chromosome polymorphic markers, showed that Ashkenazi Jews are more closely related to other Jewish and Middle Eastern groups than to their host populations in Europe. However, Ashkenazim have an elevated frequency of R-M17, the dominant Y chromosome haplogroup in Eastern Europeans, suggesting possible gene flow. In the present study of 495 Y chromosomes of Ashkenazim, 57 (11.5%) were found to belong to R-M17. Detailed analyses of haplotype structure, diversity and geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Haplotypes are coded as in Table 1. slightly lower than observed in Portuguese population at large (0.999 6 0.001; Alves et al, 2007). This high Y-STR diversity is in accordance with the findings of Nebel et al (2001) in the Middle Eastern Sephardic Jews, but contrasts with those usually observed in Ashkenazi Jews, which present much lower diversities than non-Jewish Europeans (Behar et al, 2003(Behar et al, , 2004Nebel et al, 2005). It is worth mentioning that, as it was previously found by Behar et al (2004) in Ashkenazi Jews, the average variance in allele size is higher in Portuguese Jews (1.00) than in general population [0.87; estimated from Alves et al (2007) data], reinforcing the previous observation at SNP level.…”
Section: Diversity Of Jewish Male Lineages From Ne Portugalsupporting
confidence: 90%
See 2 more Smart Citations
“…Haplotypes are coded as in Table 1. slightly lower than observed in Portuguese population at large (0.999 6 0.001; Alves et al, 2007). This high Y-STR diversity is in accordance with the findings of Nebel et al (2001) in the Middle Eastern Sephardic Jews, but contrasts with those usually observed in Ashkenazi Jews, which present much lower diversities than non-Jewish Europeans (Behar et al, 2003(Behar et al, , 2004Nebel et al, 2005). It is worth mentioning that, as it was previously found by Behar et al (2004) in Ashkenazi Jews, the average variance in allele size is higher in Portuguese Jews (1.00) than in general population [0.87; estimated from Alves et al (2007) data], reinforcing the previous observation at SNP level.…”
Section: Diversity Of Jewish Male Lineages From Ne Portugalsupporting
confidence: 90%
“…This haplogroup and in particular R1a1-M17 emerges with elevated frequencies in Ashkenazim Jews, but with rather lower frequencies in Sephardic Jews (Nebel et al, 2001(Nebel et al, , 2005Behar et al, 2003;Shen et al, 2004;Adams et al, 2008). This haplogroup is widely distributed throughout Eastern Europe: Russia, Ukraine, Poland, and Hungary, and its presence in Ashkenazim Jews is attributed to the genetic interaction of the populations of these regions with the founding communities of this rite (Behar et al, 2003;Nebel et al, 2005). Although it is a frequent lineage in the various published studies concerning Jewish populations, in this work the frequency found for this haplogroup is very low, similar to the non-Jewish Portuguese population.…”
Section: Haplogroup R1mentioning
confidence: 98%
See 1 more Smart Citation
“…40 Overall, Ashkenazi Jews exhibit a frequency of 15.3% for haplogroup R1a1a-M198. 37 Nebel et al 41 proposed, on the basis of moderate to high frequency of R1a1a in Central Asia and southern Russia/Ukraine, that these R1a1a chromosomes in Ashkenazi groups might represent vestiges of Khazars. It is thought that this Turkic tribe from Central Asia had converted to Judaism at the end of the Eighth century C.E.…”
Section: Similarity Between Pathans From Afghanistan and Pakistanmentioning
confidence: 99%
“…In addition, Jewish heritage recognizes three paternally inherited castes, Cohen, Levite and Israelite, of which the first two are considered priesthood lineages18212223. Levites comprise ~4% of the male Jewish population and display genetic evidence for multiple recent origins, with Ashkenazi Levites reported to carry a particularly high frequency (>50%) of a distinctive STR-based lineage nested within haplogroup R1a-M198 (refs 18, 24, 25). Previous studies have demonstrated that haplogroup R1a is rare in other Jewish castes, other Jewish communities and in non-Jewish groups of Near Eastern origin1821.…”
mentioning
confidence: 99%